Kesiapan Siswa Sekolah Menengah Kejuruan dalam Menghadapi Dunia Kerja di SMK Negeri 1 Bukittinggi - Mulia, Nazilatul; Rahmi, Alfi; Afrinaldi, Afrinaldi; Yusri, Fadhilla (YASIN, 2023)
Lack of knowledge about the world of work, the lack of students who work according to the program of expertise, some students follow friends in choosing majors, are not too sure whether the chosen major is correct or not, and still lack knowledge or training about the world of work. The research objective was to determine the readiness of vocational high school students to face the world of work at SMK Negeri 1 Bukittinggi. The research sample comprised 40 respondents, 21 class XII TITL students, and 19 T.GEO students. This type of research is the quantitative descriptive method of field research (field research). Quantitative descriptive is research that seeks to describe or describe a phenomenon or event that is happening. The population of this study amounted to 498 students. The technique for collecting data is a questionnaire/questionnaire with a Likert scale measurement scale. The sampling technique used random sampling. Data analysis techniques use descriptive quantitative methods. From all the data, it can be concluded that the overall average score is 57.7% with a standard deviation of 0.58 which is classified as in the medium category. Based on the research that has been done, it is known that students' readiness to face the world of work is moderate. Hopefully, this research can be used as material for future consideration in vocational schools to prepare students to face the world of work.